ASO TITRE IN ACUTE RHEUMATIC FEVER/RHEUMATIC HEART DISEASE IN PEDIATRIC AGE GROUP - DR. D. M. KULKARNI,; DR. S. A. BARDAPURKAR,; DR. S. L. NILEKAR,; DR. V. L. KULKARNI, (International Journal of Pharma and Bio Sciences, 2015)
Rheumatic fever and rheumatic heart disease remain significant causes of cardiovascular disease and mortality, particularly in the developing countries. The identification of the first attack of rheumatic fever/carditis is of paramount importance to prevent further episodes and residual cardiac damage. In the present study, we report the significance of antistreptolysin-O (ASO) test in the diagnosis of RF and RHD. The study aimed to determine ASO titre in normal children & in those with rheumatic fever. Blood samples of 200 children clinically diagnosed as ARF/RHD and of 100 normal children aged 5-15 years were screened for ASO antibodies by latex agglutination test. Seropositivity of ASO antibodies was 77% in ARF/ RHD cases and 21% in control children. A total of 41% ARF/RHD cases and 14% of control children showed an ASO titre of 200IU/ml. Seropositivity of ASO antibodies was slightly more in females than males in cases as well as control. It can be suggested from our study that ASO titre of >200IU/ml or above should be taken as a diagnostic titre in the pediatric age group of our geographic area.